Evaluation of Patient Compliance with the Use of Type II Diabetes Mellitus Medication at Clinic X Padang City - Renatalia Fika; Yonrizon; Ainun Naim; Mazaya Fadhila; Putri Ulandari (Institute of Computer Science (IOCS), 2022)
Diabetes Mellitus (DM) is a metabolic disease characterized by hyperglycemia due to defects in insulin secretion, insulin action, or both. Patient compliance is necessary to successfully treat non-communicable diseases (diabetes mellitus, hypertension, asthma, cancer, etc.), mental disorders, HIV/AIDS infectious diseases, and tuberculosis. This study aims to describe the level of adherence of patients taking DM type II medication. This cross-sectional study involved 90 patients who met inclusion and exclusion criteria. The level of patient adherence was measured using the MMAS-8 questionnaire sheet, translated into Indonesian as a research instrument. Data were analyzed using univariate and bivariate analysis to describe the frequency distribution of patient characteristics and the level of adherence. Relationship between patient characteristics and the level of adherence was tested with the chi-square test using SPSS version 23. It was found that 77 respondents (85.6%) were included in the adherent category, and 13 respondents (14.4%) were non-adherent. The low compliance rate was 13 respondents (14.4%), the moderate compliance level was 50 respondents (55.6)%, and the high compliance level was 27 respondents (30%). The results of this study indicate that patient adherence to the use of DM type II drugs at Clinic X Padang City is high. Variables that affect patient adherence to taking medication for DM type II at Clinic X Padang City are age, gender, education, employment, and income because it gets significant Value. Meanwhile, the long duration of the drug does not affect adherence to taking medication because it gets an insignificant value